Association between toxic heavy metals and noncancerous thyroid disease: a scoping review - Muhammad Ridzwan Rafi’i; Mohd Hasni Ja’afar; Azmawati Mohammed Nawi; Shahrul Azhar Md Hanif; Siti Najiha Md Asari (PeerJ)
Background Toxic heavy metals such as chromium (Cr), arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) are known to be priority pollutants due to their high degrees of toxicity and widespread presence in the environment. This review aimed to explore the association between heavy metals and noncancerous thyroid diseases by synthesizing findings from observational and experimental studies. This review addressed a critical intersection of environmental health, endocrinology, and public health. The findings would be of interest to a wide range of disciplines given the ubiquitous presence of toxic heavy metals in the environment and their potential to disrupt endocrine systems. The evidence-based information from diverse fields generated from this review will provide insights into the health implications of heavy metal exposure on thyroid function and guide the necessary interdisciplinary research and collaborative interventions. Method Three databases were searched, namely PubMed, Web of Science, and Scopus. The Arksey and O’Malley (2005) framework was used as a guide in conducting this scoping review. The reporting was carried out based on the Preferred Reporting Items for Systematic Reviews and the Meta-Analyses Extension for Scoping Reviews (PRISMA). The literature search retrieved 552 articles and 29 articles were included in the final review. Results As high as 83% of the 29 included studies followed an observational study design while the rest were experimental animal studies. Among the observational studies, two-thirds (66%) were cross-sectional studies while the rest were case-control studies (31%) and cohort studies (n = 1, 3%). Few number of studies in this review reported a significant association between Cr, As, Cd, Hg, and Pb with noncancerous thyroid diseases (2, 3, 16, 8, and 12) while another few (5, 8, 9, 5, and 11) did not show any significant association. Conclusion A heterogeneous and diverse sample population in the included studies could have potentially led to mixed findings about the association between toxic heavy metals and thyroid diseases in this review. Therefore, future research should prioritize longitudinal studies and controlled clinical trials to better elucidate the causative mechanisms and long-term impact of heavy metal exposure on thyroid health.